1999
DOI: 10.1046/j.1525-1497.1999.07238.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for undetected mental disorders in high utilizers of primary care services

Abstract: OBJECTIVE:To define the prevalence and detection rates of mental disorders among high utilizers as compared with typical utilizers, and to examine the effect of case-mix adjustment on these parameters. DESIGN:Cross-sectional study. SETTING:General internal medicine outpatient clinic associated with an urban, academic medical center. PATIENTS:From patients attending a general medicine clinic, 304 were selected randomly in three utilization groups, defined by number of clinic visits: (1) high utilizers; (2) case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
3
17
0
2
Order By: Relevance
“…Our frequent callers closely mirror patients with high rates of offi ce utilization. 3 They are often female patients who are suffering from anxiety, depression, chronic illnesses, or pain. They go to the emergency department and are hospitalized more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our frequent callers closely mirror patients with high rates of offi ce utilization. 3 They are often female patients who are suffering from anxiety, depression, chronic illnesses, or pain. They go to the emergency department and are hospitalized more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Health services researchers typically identify high utilizers by their number of visits to the offi ce. [2][3][4] Patients who come to the offi ce frequently have been described as older, divorced or widowed, members of lower socioeconomic groups, anxious and depressed, and having multiple physical and psychosocial ills and medically unexplained symptoms. 5,6 The purpose of this study was to describe frequent after-hours callers, categorize their medical problems, and examine their resource utilization.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Previous studies have shown that frequent attenders have more chronic physical conditions, 3 mental disorders [4][5][6] and psychological distress, 7 poorer health beliefs, 8 and more need of information and/or reassurance, 9 compared with non-frequent attenders. However, the use of diverse definitions of frequent attendance avoids a comprehensive interpretation of these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Many health care providers face challenges in dealing with psychological difficulties, in cancer survivors, and the inability to attend to the needs is generally demonstrated by the poor detection of psychological mood disturbance in health care setting (Lefevre et al, 1999;Schwenk, Coyne, & Fechner-Bates, 1996). Thus, understanding the extent of this problem is critical and necessary for the purposes of screening, prevention, and treatment.…”
mentioning
confidence: 99%